Role of Obstructive Sleep Apnoea in Sensorineural Hearing Loss: A Cross-sectional Study - J Shanmugh; RB Namasivaya Navin; K Gowthame; S Prabakaran; D Balaji; R Muthukumar; S Rajasekaran (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Obstructive Sleep Apnoea Syndrome (OSAS) affects millions globally. The condition significantly impacts the inner ear’s ability to transduce sound due to the essential oxygen supply required for hair cells in the cochlea. Given the increasing prevalence of OSAS, there is an urgent need for greater awareness and research on its implications for hearing health. Aim: To assess hearing functions in patients with OSAS, aiming to elucidate the relationship between the disorder and sensorineural hearing loss. Materials and Methods: A cross-sectional study was conducted at Chettinad Hospital and Research Institute, a tertiary care centre in Chengalpattu district, Tamil Nadu, India, from August 2024 to January 2025. A total of 60 participants with symptoms of Obstructive Sleep Apnoea (OSA) took part in the study. The participants were assessed using the Snoring, Tiredness, Observed apnoea, high blood Pressure, Body Mass Index, Age, Neck circumference, and Gender (STOP-BANG) questionnaire to evaluate the severity of OSA, polysomnography to confirm sleep apnoea, and pure tone audiometry to assess hearing loss. The test for association was performed using Fisher’s Exact test, and correlation was assessed through Spearman’s Correlation. Results: A total of 60 participants with symptoms of OSA took part in the study with an average age of 41.2 years. Approximately 48% of the participants were found to have a high risk of severe OSA according to the STOP-BANG scoring. About half of the participants (53.3%) were found to have sensorineural hearing loss. Only 60% of the participants exhibited symptoms of OSA such as snoring, daytime sleepiness, and tiredness. The Spearman correlation coefficient between the STOP-BANG risk grade and the presence of sensorineural hearing loss was 0.596, and with the severity of hearing loss, it was 0.576, both demonstrating a moderate correlation. Conclusion: The present research shows an association between OSA and sensorineural hearing loss, indicating that individuals with higher OSA risk scores experience more significant hearing impairment. The severity of hearing loss correlates with the elevation of OSA risk levels. Early detection and management of OSA are crucial not only for controlling the condition but also for preventing complications such as hearing loss or progression of its severity, thereby promoting better auditory health outcomes.